THE INFLUENCE OF HEALTH EDUCATION THROUGH LEAFLETS AND VIDEO MEDIA ON KNOWLEDGE ABOUT THE DANGERS OF SMOKING IN STUDENTS OF JUNIOR HIGH SCHOOL 1 PETERONGAN - Prawito, Prawito; Ibura, Djihan; Zatihulwani , Eliza Zihni (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2024)
Background: Smoking is an unhealthy habit that can cause various diseases. Health education is essential to improve understanding of the dangers of smoking. Objectives: This study aimed to evaluate the effect of health education through leaflets and video media on students' knowledge about the dangers of smoking at Junior High School 1 Peterongan. Design: This research method uses quasi-experimental methods with one group, pretest-posttest. The population is 225 students of class VII of SMPN 1 Peterongan with a sample of 56 respondents using random sampling techniques. Data were taken using a knowledge questionnaire. Data were analyzed using the Wilcoxon Test, the Asymp. Sig. (2-tailed) value was obtained at 0.000 <α 0.05, so it can be concluded that H1 is accepted, which means that there is an Effect of Health Education Through Leaflets and Video Media on Knowledge of the Dangers of Smoking in Students of Junior High School 1 Peterongan. Results: The results of the study showed that before the treatment, most respondents had a low level of knowledge, with a total of 32 people (57.1%), and no respondents had knowledge in the good category. After the treatment, most respondents had sufficient knowledge, namely 28 people (50.0%), while only a few respondents were still in the low category, namely 2 people (3.6%). Conclusion: Health education has a significant impact on students' knowledge of the dangers of smoking. Increasing knowledge about the dangers of smoking is very important for teenagers. The role of parents in supervising teenagers is also crucial to prevent smoking behavior and achieve the expected results.